Efficiency calibration of a medium resolution subsea detection system for extended sediment samples - Maragkos, F.; Tsabaris, C.; Androulakaki, E. G.; Kokkoris, M.; Pappa, F. K.; Patiris, D. L.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
N/A